2003
DOI: 10.1086/377234
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Recurrent Vulvovaginal Candidiasis, Vaginal Concentrations of Mannose-Binding Lectin, and a Mannose-Binding Lectin Gene Polymorphism in Latvian Women

Abstract: Vaginal concentrations of mannose-binding lectin (MBL) and possession of a polymorphism in codon 54 of the MBL gene were determined in 42 women with recurrent vulvovaginal candidiasis (RVVC) and 43 control subjects. Reduced vaginal MBL levels and an increased occurrence of the polymorphism were present in women with RVVC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
126
2
10

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(146 citation statements)
references
References 21 publications
8
126
2
10
Order By: Relevance
“…In the case of females, small changes in vaginal MBL appear to be related to susceptibility of individuals to recurrent vulvovaginal candidiasis (median 15·9 ng/ml in controls compared to 7·3 ng/ml in patients) [13]. MBL binds to Chlamydia trachomatis, and at low MBL concentrations (0·08 mg/ml) can inhibit C. trachomatis binding to HeLa cells [34].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of females, small changes in vaginal MBL appear to be related to susceptibility of individuals to recurrent vulvovaginal candidiasis (median 15·9 ng/ml in controls compared to 7·3 ng/ml in patients) [13]. MBL binds to Chlamydia trachomatis, and at low MBL concentrations (0·08 mg/ml) can inhibit C. trachomatis binding to HeLa cells [34].…”
Section: Discussionmentioning
confidence: 99%
“…This was proposed by Kruse et al (131), who demonstrated that patients with MBL levels <100 ng/mL had a higher abortion rate. Some urogenital infections such as vulvovaginitis, herpes simplex virus-2 infection, vulvovaginal candidiasis and vestibulitis appear to be linked to low MBL levels in comparison to healthy controls (132)(133)(134). Downstream complement deficiencies are typically associated with recurrent invasive infections of Neisseria meningitidis and gonorrhea (135).…”
Section: Infectionsmentioning
confidence: 99%
“…The serum concentration of MBL normally ranges from 0.01 to 10 mg/ml, 32,53 and as an acute-phase protein, MBL can increase up to threefold under inflammatory conditions. 54 MBL is also present in synovial fluid and amniotic fluid and in lung and vaginal lavages, [55][56][57][58][59] where it behaves as an acute-phase reactant in individuals with 'sufficient' (wild-type) MBL genotypes. 54 We therefore presume that binding of MBL to the autologous cells most likely occurs at inflammatory loci, where a local elevation of extravascular MBL and a concomitant influx of immune cells are to be expected.…”
Section: Mbl Interacting With Tlr4 Regulates Lps Signalingmentioning
confidence: 99%